If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y = 7y + -45 Reorder the terms: 8y = -45 + 7y Solving 8y = -45 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 8y + -7y = -45 + 7y + -7y Combine like terms: 8y + -7y = 1y 1y = -45 + 7y + -7y Combine like terms: 7y + -7y = 0 1y = -45 + 0 1y = -45 Divide each side by '1'. y = -45 Simplifying y = -45
| 3t^3-9t+6=0 | | 27c^4-125c=0 | | 9x^2-5x=3 | | -8=-x-4 | | 3x=2-4y | | 10y=5y-5 | | 4(3x+4)=52 | | 35x^2-16x-3=0 | | 4x+3=-45 | | 9x+14=-67 | | w^2+4w-x^2+4=0 | | -7y+5(y-4)=-18 | | 6x+13=-5 | | 2x-0.35=.20 | | 4x+6=-62 | | 7(4x+1)=3(12x-3) | | 92x+31=72 | | -3x+9=30-6x | | 2c/10=24 | | (5c+6)(5c-6)=0 | | 2x^2-4x-44=0 | | 53a-143=42a+8 | | 3x=6-x | | 18-t/20=-9 | | 3s/5=-21 | | x^2-15x+9=0 | | n(n-6)=7 | | 25x(x+4)=10x-81 | | 17b+3=-422 | | 18=18y-18 | | 3c+45=7.2-6c | | 7m^2-2m+2=0 |